Exploring the costs and effectiveness of the Drug and Alcohol Withdrawal Network: a home-based alcohol and other drug withdrawal service - Wright, Cameron; Norman, R.; Varhol, R.; Davis, J.; Wilson-Taylor, E.; Dorigo, J.; Robinson, S. (C S I R O Publishing, 2018)
The Drug and Alcohol Withdrawal Network (DAWN) is a home-based withdrawal service based in Perth, Western Australia. Literature on outcomes, costs and client attitudes towards this type of home-based detoxification in Australia is sparse. Therefore, this study assessed these factors for clients enrolled over a 5-year period (July 2011-June 2016). Client experience was explored through semi-structured interviews with 10 clients. Over the study period, 1800 clients (54% male, mean age 38 years) were assessed, and there were 2045 episodes of care. Although most first-episode clients (52%) listed alcohol as the primary drug of concern, the proportion listing methamphetamine increased from 4% in 2011-12 to 23% in 2015-16. In 94% (n=639) of withdrawal detoxification episodes with completed surveys, clients used their 'drug of primary concern' most days or more often at baseline; this had reduced to 23% (n=149) at the conclusion of detoxification. Five-year direct costs were A$4.8million. Clients valued the person-centred holistic approach to care, including linking with other health providers. Barriers included low awareness of the program and difficulties finding an appropriate support person. Further exploration of cost-effectiveness would substantiate the apparently lower per client cost, assuming medical suitability for both programs, for home-based relative to inpatient withdrawal.